2020
DOI: 10.5146/tjpath.2020.01490
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer: clinicopathological, immunohistochemical and radiological study

Abstract: Objective: To evaluate the pathological and radiological features, immunohistochemical profile and treatment methods of primary male breast carcinoma cases diagnosed at our center. Material and Method: The pathology archive between 2006 and 2019 was reviewed and the data of 27 male patients diagnosed as primary breast cancer were retrospectively evaluated. Results: The age of the patients ranged between 40-86 years. The left breast was involved in 17 patients. The mean tumor diameter was 2.35 ± 1.09 cm. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our study attempted to present the radiological and clinicopathological characteristics of MBC patients in the western region of KSA. According to imaging features of the 20 patients who had an ultrasound, 16 (80%) lesions were presented as hypoechoic solid masses with irregular margins [ 74 ]; in our cases, also, majority of cases have ill-defined margins and hypoechoic solid mass, respectively.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our study attempted to present the radiological and clinicopathological characteristics of MBC patients in the western region of KSA. According to imaging features of the 20 patients who had an ultrasound, 16 (80%) lesions were presented as hypoechoic solid masses with irregular margins [ 74 ]; in our cases, also, majority of cases have ill-defined margins and hypoechoic solid mass, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…We have found only 1 patient who had a well-defined mass, and 5 patients had ill-defined mass out of total 17 screened cases that is closely similar to the data reported by Doyle et al, where they found that out of 13 patients who underwent mammography, 6 of them had an ill-defined breast mass and 2 had a well-defined breast mass visualized [ 73 ]. The time interval between the onset of complaints and admittance to hospital ranged from three months to two years [ 74 ]. The median duration of the evolution of the MBC symptoms and signs was 9 months [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%